ANALISIS DAMPAK OTONOMI DAERAH TERHADAP STRATEGI PENGEMBANGAN PERGURUAN TINGGI SWASTA (PTS) DI KABUPATEN SLEMAN - Rudy Badrudin (Muhammadiyah University Press, 2008)
This research analyze the effect of regional autonomy to the interest of college’s student candidate to continue studying in Sleman Regency which research’s samples for major program’s chosen was Accounting, Management, and Economics in UII, UAJY, UPNVY, and STIE YKPN. The result of research with Boston Consulting Group (BCG) Matrix shows that each major program in four universities and college was in different quadrant. Therefore, each university and college has to choose different development strategic specifically even for each major programs in each university and college, so that the major programs in four universities and college in Sleman Regency could grow and rise.